PENGARUH MUHADHARAH TERHADAP KETERAMPILAN BERBICARA BAHASA INDONESIA PESERTA DIDIK MAN INSAN CENDEKIA OKI - Afriansyah, Afriansyah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2019)
This research discusses about muhadharah effect to speaking skills in Indonesian language to students of MAN Insan Cendekia OKI. The aim of this research is to identify muhadharah effect to speaking skills in Indonesian language to students of MAN Insan Cendekia OKI. To get the result, the writer used descriptive analythical method and analyzed by the theory of speak skills factors of Arsjad G. Maidar. The data sources are obtained from observation, video of muhadharah, and muhadharah participant friends interview. After researcher did the research from 8 samples, the reasearcher found that muhadharah can improve speaking skill in Indonesian language to students of MAN Insan Cendekia OKI